Analysis Of Presentation Of Sharia Financial Statements According To Psak 101 At Pt. Mandiri Sharia Bank - Fera Riske Anggita; Tommy Kuncara (Publisher Cv. Inara, 2021)
The presentation of Islamic Financial Statements has been regulated in PSAK 101 and every bank needs to refer to it. As we know, PT Bank Syariah Mandiri is the number 1 largest Islamic bank in Indonesia and other information obtained by researchers, PT Bank Syariah Mandiri will merge with 2 other Islamic state-owned banks, namely PT Bank BNI Syariah and PT Bank BRI Syariah. Therefore, researchers are interested in examining whether the financial statements of PT Bank Syariah Mandiri are appropriate in applying the application of Financial Accounting Standards 101. The types of data used are qualitative and quantitative data, the data used are general company information and company financial statement information in 2019. Sources the data used is secondary data. The data collection method is literature study. In the financial statements of PT Bank Syariah Mandiri, the bank has reported all components of the financial statements in PSAK 101. In the Statement of Financial Position PT Bank Syariah Mandiri does not include the Istishna Assets in Settlement and Salam Receivable accounts in the Statement of Financial Position, but in PSAK 101 Paragraph 61 explains Statement of Financial Accounting Standards 101 does not regulate the composition or format of presentation of statement of financial position items. PT Bank Syariah Mandiri continues to present relevant information on the Statement of Financial Position. However, in PSAK 101 Paragraph 61 explaining the Statement of Financial Accounting Standards 101 does not regulate the composition or format of the presentation of the statement of financial position. PT Bank Syariah Mandiri continues to present relevant information on the Statement of Financial Position. However, in PSAK 101 Paragraph 61 explaining the Statement of Financial Accounting Standards 101 does not regulate the composition or format of the presentation of the statement of financial position. PT Bank Syariah Mandiri continues to present relevant information on the Statement of Financial Position.